Предмет: Алгебра,
автор: KGlubokaya
3tg^2 4x - 2ctg(п/2 - 4х) = 1
Ответы
Автор ответа:
0
3tg²4x-2ctg(π-4x)=1
3tg²4x-2tg4x-1=0
Обозначим tg4x=y.
3y²-2y-1=0
D=4+12=16=4²
y₁=(2-4)/6=-2/6=-1/3
y₂=6/6=1
tg4x=-1/3
4x=arctg(-1/3)+πn
4x=-arctg1/3+πn
x=-¹/₄ arctg1/3 + (π/4)n
tg4x=1
4x=arctg1+πn
4x=π/4 + πn
x=π/16 + (π/4)n
3tg²4x-2tg4x-1=0
Обозначим tg4x=y.
3y²-2y-1=0
D=4+12=16=4²
y₁=(2-4)/6=-2/6=-1/3
y₂=6/6=1
tg4x=-1/3
4x=arctg(-1/3)+πn
4x=-arctg1/3+πn
x=-¹/₄ arctg1/3 + (π/4)n
tg4x=1
4x=arctg1+πn
4x=π/4 + πn
x=π/16 + (π/4)n
Автор ответа:
0
только не п/8, а п/16
Автор ответа:
0
спасибо, исправлено
Похожие вопросы
Предмет: Геометрия,
автор: bekkerg86
Предмет: Биология,
автор: hasenkoanna69
Предмет: История,
автор: aleksandrapech
Предмет: Математика,
автор: tatyana200
Предмет: Математика,
автор: КисаВэлентайн